Distribution of Household Income in the Czech Republic in 1988-1996: Readjustment to the Market - Jirí Vecerník (Luxembourg Income Study (LIS), 1999)
In the second half of the twentieth century, the country located in the troubled heart of Europe experienced two radical conversions of regimes. In 1948 peaked the communist revolution which continued in its most repressive form until the mid-1950s. In 1990, economic reform involving large privatization and liberalization opened the road 'back to capitalism'. The first regime change - the communist 'revolution' - externally manifested ideology of equality but internally followed the Soviet model of how to feed more workers from a smaller bread. The second regime change - the capitalist 'counter-revolution' - aimed to de-equalize earnings, re-introduce market competition and re-create new sources of income, especially from business. In this paper, we concentrate only on the second political change. Available data give us a unique opportunity to investigate changes introduced by political democracy and a market system. In the first part, the growing difficulties of income surveys are reflected upon. In the second part, we ask whether income indicators do not partly reflect political regime and economic situation. In the third part, change in income distributions and factors is analyzed. In the fourth part, we concentrate on the redistribution of income through taxes and social benefits. And in the fifth part, we try to resume adjustment to the market by using comparative data from Western countries, using mostly the LIS database.
Keywords: 330; Einkommensverteilung; Haushaltseinkommen; Tschechische Republik